Publications of the Modern Language Association of America (PMLA): tomo 62 (1947), tomo 63 (1948). - Alatorre, Antonio (Nueva Revista de Filología Hispánica (NRFH), 1956)
Se reseñó: PMLA: tomo 62 (1947), tomo 63 (1948).